Elena Redaelli - Corvis ST Biomarkers in Healthy and Keratoconic Eyes: Clinical and Numerical Evaluation - Redaelli, Elena (Jornada de Jóvenes Investigadores del I3A, 2022)
CORVIS ST BIOMARKERS IN HEALTHY AND KERATOCONIC EYES: CLINICAL AND NUMERICAL EVALUATION